Functionalized asphalt mixtures: Photocatalytic, superhydrophobic and self-cleaning properties - Rocha Segundo, I. (2017)
Functionalization of road pavement asphalt mixtures provides new capabilities that can mitigate problems like air pollution and road accidents. In this research, nano-TiO2 and micro-ZnO were deposited through an aqueous solution by spraying it over the surface of asphalt mixture samples in order to promote the photocatalytic, superhydrophobic and self-cleaning capabilities. Tested by degradation of Rhodamine B, to assess the Photocatalytic Efficiency, and by Water Contact Angle (WCA), to assess the wettability of the materials, this technique can be used to promote these multifunctional capabilities in asphalt mixtures. With these enhanced surface characteristics, road safety and the environment, through pollutants degradation like NOx and SO2, will be improved.